Pengaruh Literasi Keuangan, Kemampuan Finansial Dan Teknologi Informasi Terhadap Minat Investasi Saham (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Metro) - Ash Sidiq, Muhammad Maulana; Septiana, Nani (Jurnal Manajemen DIVERSIFIKASI, 2023)
Lack of financial literacy is one of the causes of financial problems, as economics and business students should have good financial literacy, financial ability possessed by students is one of the factors that become obstacles for students to start investing and the existence of information technology that is increasingly modern today become facilities that make it easier for students to make investments. The purpose of writing this article is to determine the effect of financial literacy, financial ability and information technology on interest in stock investment. research method using a survey study tested using multiple regression analysis, partial test, stimulant test and the coefficient of determination test. The results of the study show that all dependent variables including financial literacy, financial ability and information technology have a positive and significant influence partially and simultaneously on stock investment interests of students of the Faculty of Economics and Business, University of Muhammadiyah Metro. it can be concluded that the higher the financial literacy, the financial ability of students and the more understanding of information technology, the higher the interest of students in investing in stocks.